Take a chance, Gramps! - Okimoto, Jean Davies (Boston : Joy Street Books, 1990)
Twelve-year-old Jane and her grandfather, both of whom have suffered losses, help each other reach out, make new friends, and change their lives.
Booklist.
Horn Book.
School Library Journal.
6.0
6.2
3-6.
Keywords: Friendship -- Fiction; Grandfathers -- Fiction; Loss (Psychology) -- Fiction; Friendship -- Fiction; Grandfathers -- Fiction; Loss (Psychology) -- Fiction